Affectivity of Zatoria multiflora Boiss extracts Against Bacteria - Rahman, M Ur; Gul, S; Odhano, EA; Hafeez, Ir; Tareen, RB (Bangladesh Journal of Scientific and Industrial Research, 2011)
The extracts of Zatoria multiflora Boiss were evaluated for prospective antibacterial activity against gram negative and gram positive bacteria. Cefoperazone is used as antibacterial reference drug. The activity of ethanol and methanol extract varied from organism to organism. The inhibitory effect of both the extracts and their 50/50 combination was more pronounced against gram positive bacteria. The MIC and MBC values were in the range of 1.718-6.25 and 2.832-6.25 mg/ml respectively. Significant (p=0.05) synergistic effect of combination of EtOH and MeOH extracts was recorded against Staphylococcus aureus ATCC 29213, Staphylococcus aureus ATCC 25923 while additive effect against rest of the bacterial strains. The present studies provide evidences for presence of antibacterial elements in alcoholic extracts and recommends for more exploration for it use against bacterial diseases. Key words: Extracts; Zatoria multiflora Boiss; Antibacterial; MIC; MBC; Synergistic. DOI: http://dx.doi.org/10.3329/bjsir.v46i1.3652 Bangladesh J. Sci. Ind. Res. 46(1), 105-110, 2011